Comprehensibility assessment using the Karlsruhe comprehensibility concept - Susanne Göpferich (JoSTrans: The Journal of Specialised Translation)
This article makes a contribution to text and translation quality assessment in the functionalist paradigm. It presents a communication-oriented framework for the evaluation of pragmatic texts including their translations with regard to their comprehensibility as one of the central factors of their skopos adequacy. It is based on the results of comprehensibility research gained both in the field of cognitive science (schema theory and theory of mental models) and in the fields of educational psychology (the four comprehensibility dimensions presented by Langer et al. and Groeben) and linguistics. It also includes results from communication theory and semiotics. In the resulting framework a distinction is made between six comprehensibility dimensions, 'perceptibility,' 'simplicity,' 'structure,' 'correctness,' 'concision,' and 'motivation.' Requirements derived from the latter four of these dimensions do not only have to be fulfilled by the textual code itself, but also by the mental models to be conveyed by the code.